Mixed-integer optimal control for multimodal chromatography - Bock, Hans Georg; Cebulla, Dominik H.; Kirches, Christian; Potschka, Andreas (Computers & chemical engineering, 2021)
Multimodal chromatography is a powerful tool in the downstream processing of biopharmaceuticals. To fully benefit from this technology, an efficient process strategy must be determined beforehand. To facilitate this task, we employ a recent mechanistic model for multimodal chromatography, which takes salt concentration and pH into account, and we present a mathematical framework for the optimization of chromatographic processes. This framework also includes the use of discrete process controls in order to cover a wider range of chromatographic applications. We describe a procedure to numerically solve the resulting nonlinear mixed-integer optimal control problems. We discuss results of computational experiments, covering the cases where one wants to optimize the yield of the product or the batch-cycle time under specified purity requirements. The results indicate that a good separation can be achieved in a two-component system and that both salt concentration and discrete pH play an important role within the purification process.